2014
DOI: 10.1177/1461444814531692
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone distraction while studying

Abstract: The mobile phone is a breakthrough advance for human communication. But with the plethora of choices available via smartphone, individuals who are deficient in self-regulation or with a propensity for addiction may face challenges in managing these choices strategically. To examine this potential dysfunctional aspect, we examined the effect of multitasking when studying or doing homework and found that both frequency and attention to texting and social media were positively related to mobile phone interference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
122
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 158 publications
(141 citation statements)
references
References 43 publications
8
122
0
4
Order By: Relevance
“…In line with previous studies on university students' time spent on communication and media activities (Calderwood, Ackerman, & Conklin, 2014;David et al, 2014;, this study identifies three communication contexts of media multitasking: (1) social-interaction activities driven by social needs, which are comprised of face-to-face communication, phone and video chat, texting, and social networking; (2) media-based entertainment activities driven by relaxation, emotional, and entertainment needs, including listening to music, watching TV or videos online, and playing video games; and (3) cognitive activities motivated by cognitive needs, mainly reading and studying (in our sample of university students).…”
Section: Media Multitasking Among University Students and Its Motivatsupporting
confidence: 58%
See 4 more Smart Citations
“…In line with previous studies on university students' time spent on communication and media activities (Calderwood, Ackerman, & Conklin, 2014;David et al, 2014;, this study identifies three communication contexts of media multitasking: (1) social-interaction activities driven by social needs, which are comprised of face-to-face communication, phone and video chat, texting, and social networking; (2) media-based entertainment activities driven by relaxation, emotional, and entertainment needs, including listening to music, watching TV or videos online, and playing video games; and (3) cognitive activities motivated by cognitive needs, mainly reading and studying (in our sample of university students).…”
Section: Media Multitasking Among University Students and Its Motivatsupporting
confidence: 58%
“…Media multitasking has become increasingly popular thanks to the versatility and accessibility of computers, smartphones, and tablets, which allow for the seamless integration of work, play, and social interaction (e.g., Carrier, Cheever, Rosen, Benitez, & Chang, 2009;David et al, 2014;Rosen, Mark Carrier, & Cheever, 2013;Srivastava, 2013). A recent investigation in the U.S. (David et al, 2014) revealed the major communication and media activities of undergraduate students on a typical day based upon self-report of 992 respondents.…”
Section: Media Multitasking Among University Students and Its Motivatmentioning
confidence: 99%
See 3 more Smart Citations